Projeto de controladores tolerantes a falhas baseados em observador : uma abordagem em faixas de frequência finita - Caio Mariano da Silva Anastácio (2021)
This work proposes to fill an existing gap in the literature by introducing a methodology to fault-tolerant control based on observer design in predefined frequency ranges with guar- anteed H-infinite performance for continuous-time switched systems. The proposed approach makes use of the states and the estimation fault from the synthesized observer to compose a control law, which ensures effectiveness in rejecting external disturbances and compen- sating for the effects of faults in low, middle and high frequency domains. Furthermore, to ensure the asymptotic stability of the switched system, the switching signal respects the mode-dependent average dwell time (MDADT) condition, ensuring that the system remains a minimum time in each mode and avoiding instabilities concerning arbitrary switching. The problem is structured in such a way that, in closed-loop, the observer and the controller can be synthesized separately. For this purpose, initially, the proposed ob- server is designed to obtain the estimates of states and faults in specific frequency ranges from the generalized Kalman-Yakubovich-Popov lemma. Subsequently, the fault-tolerant controller with H-infinite guaranteed cost is designed, ensuring closed-loop stability for switched systems under MDADT constraints. In both designs, the conditions are described in lin- ear matrix inequalities form. Illustrative examples taken from the literature are used to demonstrate the effectiveness and applicability of the proposed approach.